Solidaritas Organisasi Fatayat Tulungagung Perspektif Kurt Bayertz - Kendima Aprilia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Fatayat Nahdlatul Ulama as a young women's organization that seeks to provide answers to issues that consider women unable to contribute to society, for these problems Fatayat seeks as a dressing room for women to channel real abilities in society, with the Fatayat organization, women in society are considered capable in various activities religiously, socially, economically, politically and culturally. This study aims to determine the solidarity movement of the Fatayat organization through the perspective of Kurt Bayertz solidarity. This research is of a qualitative descriptive type. Research data were obtained through interviews, observations and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The results showed that Fatayat's activities can be said to be the embodiment of the solidarity movement. Fatayat solidarity is described as universal solidarity, social solidarity, citizen solidarity and political solidarity. Fatayat solidarity relevant to Kurt Bayertz solidarity includes (1) Universal solidarity arises because of the bonding of the organization's vision and mission and is followed by all internal and external parties. (2) Social solidarity occurs due to social relations with external parties. (3) Citizen solidarity is formed by spontaneity such as fundraising and disaster care activities. (4) Political solidarity occurs with external recognition of the existence of Fatayat NU.